FAKOR-FAKTOR YANG MEMPENGARUHI PERSEPSI PETANI TERHADAP PERAN SERTIFIKASI INDIKASI GEOGRAFIS KOPI ARABIKA DI DESA CATUR, KECAMATAN KINTAMANI, KABUPATEN BANGLI - Jampur, Robinardus; Yudiarini, Nyoman; Pratiwi, Luh Putu Kirana (Fakultas Pertanian Universitas Mahasaraswati Denpasar, 2019)
Research on the factors that influence the perception of the role of farmers certified Arabica coffee geographical indication in the village of Catur, Kintamani Distrit, Bangli Regency the efforts to increase the productivity of coffee farmers Arabica. This research aims to: (1) find out the perception of the role of Arabica coffee growers certification of geographical indications Arabica coffee in the village of Catur, Kintamani Distrit, Bangli Regency, and (2) find out the factors that influence the perception of farmers of the role of certification of geographical indications Arabica coffee. This research uses descriptive qualitative and quantitative methods. Analysis on the analysis with qualitative methods with measurement scales use likert scale, respondents answers and analysis the second objective in the analysis with quantitative methods with measurement scale using the SPSS version 17.0. The results of this research show that the perception of the role of Arabica coffee growers certification of geographical indications was very good. It can be seen from the 4 indicators natural factors, human factors, characteristics and quality of the coffee. Of the fourth such indicators research index of perception of farmers very good is at number 86.6%. Factors that influence the perception of the role of farmers certification berpengruh geographical indications are positive and significant. The influence by 5 indicators, sale price, production, labor, and land area, capital.